Oral exposure to lead for Japanese children and pregnant women, estimated using duplicate food portions and house dust analyses - Mayumi Ohtsu; Nathan Mise; Akihiko Ikegami; Atsuko Mizuno; Yayoi Kobayashi; Yoshihiko Nakagi; Keiko Nohara; Takahiko Yoshida; Fujio Kayama (Komiyama Printing Co. Ltd, 2019)
Abstract Background Lead is a toxic metal abundant in the environment. Consumption of food contaminated at low levels of lead, especially by small children and pregnant women, raises a health concern. Methods Duplicated food portions and drinking water were collected over 3 days from 88 children and 87 pregnant women in Shimotsuke, Tochigi, Japan. Participants were recruited in this study between January 2014 and October 2015. Dust was also collected from their homes. Lead concentrations were measured and consequent oral lead exposure levels were estimated for this population at high risk to environmental toxicants. Lead concentrations of peripheral and cord blood, taken from children and pregnant women, and were also analyzed. Results Lead concentrations in food, drinking water, and house dust were low in general. Oral lead exposure to lead was higher for children (Mean ± SEM; 5.21 ± 0.30 μg/kg BW/week) than in pregnant women (1.47 ± 0.13 μg/kg BW/week). Food and house dust were main sources of lead contamination, but the contribution of house dust widely varied. Means ± SEM of peripheral and cord blood lead concentrations were 0.69 ± 0.04 μg/dL and 0.54 ± 0.05 μg/dL, respectively for pregnant women and 1.30 ± 0.07 μg/dL (peripheral only) in children. We detect no correlation between smoking situations and blood lead concentration in pregnant women. Conclusion We conclude that oral lead exposure levels for Japanese children and pregnant women were generally low, with higher concentrations and exposure for children than for pregnant women. More efforts are necessary to clarify the sources of lead contamination and reduce lead exposure of the population at high risk even in Japan.